Study and Simulation of the Density of the Incident Solar Flux on the Walls of a Building in Adrar, Algeria - Oudrane, A.; Aour, B.; Zeghmati, B.; Chesneau, X.; Massaoud, H. (Engineering, Technology & Applied Science Research, 2017)
In this work, we studied the effect of external climatic conditions on the evolution of the daily solar flux incident on the walls of a building located at Adrar region in the South of Algeria. This building is designed for heating or air conditioning applications. Numerical simulations allowed to compare the variation of the incident solar flux over a full day on the south, east, north and west walls of the building to the values of the solar flux on a horizontal wall (the outer ceiling). The horizontal global solar flux is calculated using a Gaussian sinusoidal function. The simulations were carried out in the case of a building located in a desert zone. The results of the numerical simulation showed the effect of the orientation of the building on the evolution of the incident daily solar flux.